PENGARUH PENGETAHUAN INVESTASI DAN EKSPEKTASI PENDAPATAN TERHADAP KEPUTUSAN INVESTASI EMAS PADA PT (Persero) PEGADAIAN CABANG ENDE - Perpetua Rumyaan dan Gabriel Tanusi; Gabriel Tanusi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims to determine and analyze the influence of investment knowledge factors and income expectation on gold investment decisions at PT Pegadaian Ende branch. This type of research includes associative research. The total population is 13.382 customers with a sample size of 99 customers. Data collection techniques use questionnaires and interviews. Data analysis technique uses multiple linier regression. This research results show that investment knowledge has a positive and significant influence on gold investment decisions at PT. Pegadaian Ende branch with an influence of 34,40 %. Income expectations has a positive and significant influence on gold investment decisions at PT. Pegadaian Ende branch with an influence of 32,10 %